Loneliness as mediator of the relation between personality and child behaviour problem among preadolescents - Chua, Yee Chii (2013)
Previous studies have separately link personality traits and loneliness to child behaviour problems. But, little known about the relatively significant for each of the variance they may share. The present study starts from the premise to identify the mediating role of loneliness between the relations of personality traits and child behaviour problems among preadolescents, and also focus on the gender differences in personality traits, loneliness and child behaviour problems. A total of 622 primary school children from aged 10-12 years old were recruited. There are three questionnaires used in this study, which is Revised Junior Eysenck Personality Questionnaire – Short Form (JEPQR-S), Loneliness and Social Dissatisfaction Questionnaire (LSDQ), Child Behaviour Checklist (CBCL). The finding showed significant mediating role of loneliness between the relations of neuroticism and internalizing behaviour problems. The result also showed significant gender differences in neuroticism, (t(620) = -5.330, p < .05) and both social (t(620) = -2.348, p < .05) and emotional loneliness (t(620) = -2.165, p < .05). Therefore, it is necessary to investigate the unique and overlapping association from personality and loneliness to child behaviour problems, especially in internalizing and externalizing behaviour problems among preadolescents.